Montmorillonite powder combined with liquid dressing and nursing management for a patient with bacterial pneumonia complicated by perianal incontinence dermatitis (1例细菌性肺炎并发肛周失禁性皮炎患者采用蒙脱石散联合液体敷料换药的护理体会) - LI Ying (李影); REN Yaxing (任亚星); YUE Yuzi (岳玉姿); ZHANG Ning (张宁); HOU Pengxiao (候朋晓); LIU Haihan (刘海涵); HAN Jianping (韩建萍) (中西医结合护理)
This paper reviewed the clinical data of a patient with bacterial pneumonia who developed perianal incontinence dermatitis during treatment. The patient was treated with Montmorillonite powder combined with liquid dressing. on the basis of routine perianal care, the dressing exchange method was improved, and the individualized scheme of Montmorillonite powder combined with liquid dressing was adopted. In addition, multidisciplinary consultation and health education were carried out to improve the wound healing, reduce the pain and improve patient’s quality of life. (本文总结1例细菌性肺炎并发肛周失禁性皮炎患者采用蒙脱石散联合液体敷料换药的护理经验。在加强肛周基础护理基础上, 护理人员运用蒙脱石散联合3M液体敷料进行肛周换药, 并通过多学科会诊, 加强健康教育, 提高依从性, 促进伤口快速愈合, 减轻患者的痛苦, 提高生活质量。)